2021
DOI: 10.3897/natureconservation.43.62864
|View full text |Cite
|
Sign up to set email alerts
|

Natural strongholds for red squirrel conservation in Scotland

Abstract: The Eurasian Red Squirrel (Sciurus vulgaris) is under threat from the invasive North American eastern Grey Squirrel (Sciurus carolinensis) with 80% of the remaining red squirrel populations in the British Isles found in Scotland. In this study we develop a spatially explicit mathematical model of the red and grey squirrel system and use it to assess the population viability of red squirrels across Scotland. In particular, we aim to identify existing forests – natural strongholds for red squirrels – that can su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The native prey is, however, suppressed in the presence of the native predator in the habitat where the invasive competitor does not occur, suggesting an alternate mechanism. In the absence of pine martens, red squirrels are thought to be able to persist in conifer plantations owing to a competitive advantage over grey squirrels [ 20 ]. Thus, in conifer plantations, the red squirrel does not benefit from competitive release from grey squirrels following pine marten recovery but is subject to predation by the shared predator [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The native prey is, however, suppressed in the presence of the native predator in the habitat where the invasive competitor does not occur, suggesting an alternate mechanism. In the absence of pine martens, red squirrels are thought to be able to persist in conifer plantations owing to a competitive advantage over grey squirrels [ 20 ]. Thus, in conifer plantations, the red squirrel does not benefit from competitive release from grey squirrels following pine marten recovery but is subject to predation by the shared predator [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our multi-species approach provides key insights into factors driving the occurrence and interactions of a complex and conservationally important interaction network which were not otherwise evident. For example, previous research has suggested that interactions between red and grey squirrels depend on habitat alone, with predictions ranging from complete extirpation of the native inferior competitor in native broadleaf woodlands to the persistence of the inferior native competitor in large commercial conifer plantations [ 11 , 20 ]. This has led to recommendations that national conservation strategies for red squirrels should focus on the planting of commercial conifer plantations as opposed to native broadleaf forests, where grey squirrels have a competitive advantage [ 11 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations